Periodicity, Stability, and Boundedness of Solutions to Certain Second Order Delay Differential Equations - A. T. Ademola; B. S. Ogundare; M. O. Ogundiran; O. A. Adesina (International Journal of Differential Equations)
The behaviour of solutions to certain second order nonlinear delay differential equations with variable deviating arguments is discussed. The main procedure lies in the properties of a complete Lyapunov functional which is used to obtain suitable criteria to guarantee existence of unique solutions that are periodic, uniformly asymptotically stable, and uniformly ultimately bounded. Obtained results are new and also complement related ones that have appeared in the literature. Moreover, examples are given to illustrate the feasibility and correctness of the main results.